An empirical study on the impact of charitable medical care on residents’ health level - Han, Boxun; Zhang, Qilin (Frontiers in Public Health, 2025)
IntroductionHealth is a crucial foundation for personal growth and the realization of a better life. As an organic part of China’s multitiered medical security system, charitable medical care has an important regulatory effect on the health level of residents. However, the improvement in residents’ health level by charitable medical care remains to be validated.MethodsBased on the panel data of the China Family Panel Studies (CFPS 2012–2020), this study establishes an evaluation index system for residents’ health level, empirically analyses the impact of charitable medical care on residents’ health level, and explores in-depth the transmission mechanism therein.ResultsThis research shows: First, an increase in the level of charitable medical donations can significantly improve the health level of residents. After conducting strict robustness tests, this conclusion still holds. Second, the accessibility and quality of medical services are the paths through which charitable medical care affects residents’ health level, and both play a mediating role. Finally, in the heterogeneity test, for groups of residents with higher levels of trust, lower annual household income, and higher total medical expenses, charitable medical care has a stronger promoting effect on their health level.DiscussionThese research results provide empirical evidence and policy implications for the optimization and reform of China’s medical security system in the context of the Healthy China Strategy.